2007
DOI: 10.1017/s0033291707002139
|View full text |Cite
|
Sign up to set email alerts
|

Unhappiness, health and cognitive ability in old age

Abstract: Background. To test whether scores on depression inventories on entry to a longitudinal study predict mental ability over the next 4-16 years.Method. Associations between scores on the Beck Depression Inventory and on tests of intelligence, vocabulary and memory were analysed in 5070 volunteers aged 49-93 years after differences in prescribed drug consumption, death and drop-out, sex, socio-economic advantage and recruitment cohort effects had also been considered.Results. On all cognitive tasks Beck scores on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 20 publications
2
15
1
Order By: Relevance
“…In our study, the lagged and the change depressive symptoms as well as the lagged cognitive function were related significantly to life satisfaction, which is consistent with the findings of previous studies (Berg et al 2006;Rabbitt et al 2008). The results suggest that an impairment of emotional or cognitive function later life affects subjective well-being or successful aging.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the lagged and the change depressive symptoms as well as the lagged cognitive function were related significantly to life satisfaction, which is consistent with the findings of previous studies (Berg et al 2006;Rabbitt et al 2008). The results suggest that an impairment of emotional or cognitive function later life affects subjective well-being or successful aging.…”
Section: Discussionsupporting
confidence: 93%
“…Psychological health is more related to subjective wellbeing. Previous studies have found a significant relationship between depressive symptoms and both cognitive function and life satisfaction (Berg et al 2006;Rabbitt et al 2008;Hsu 2009). …”
Section: Physical Mental and Social Dimensions Of Health And Life Smentioning
confidence: 97%
“…However, self-report measures are commonly used to assess depressive symptoms in population-based studies and earlier studies point to the effects of even subclinical levels of depressive symptoms on functioning and cognitive performance (10, 12, 59). Moreover, by using the CES-D, we were able to show that even mild depressive symptoms in a non-patient sample are still associated with poorer cognitive function.…”
Section: Resultsmentioning
confidence: 99%
“…Yet cognitive functioning remains an essential determinant of subjective well-being among persons living 100 years and longer [47]. Investigators have acknowledged that normative age-graded cognitive decline suppresses key markers of biopsychosocial well-being including individual autonomy, social involvement, and functional capacity among very old adults [811]. This suggests that poor cognitive performance may alter how exceptionally long-lived persons appraise life.…”
Section: Introductionmentioning
confidence: 99%
“…Life satisfaction has commonly been recognized as an affective-cognitive construct [3, 4, 11, 17, 18]. The developmental past has been reported as a critical “anchor period” and key mediating indicator of positive emotionality [24, 27].…”
Section: Introductionmentioning
confidence: 99%